Case study of the use of institutional information for decision-making in the strategic planning process at a community college - Crossen, Rosanne Trovato, author; Davies, Timothy Gray, advisor; Harbour, Clifford, committee member; Hall, Bruce, committee member; Klass, Gary M., committee member (Colorado State University. Libraries, 2004)
This case study's purpose was to better understand how one community college's leaders used institutional information when making decisions for their strategic planning process. Of particular interest was how these decision-makers used institutional information to shape their decisions while establishing strategic priorities. The study goals were to explore the strategic planning process and evaluate how institutional information was used for decision-making. The study described the strategic planning process and how it operated; discovered the institutional information types available and how leaders used this information to make strategic plan decisions; and gained insight into how using institutional information during the strategic planning process impacted the college's decision-making processes. Higher education institutions may address accountability demands and pressures to explain how decisions are made, including those pertaining to the planning process, through institutional research. The case study findings were presented as a strategic planning process chronology and discussions concerning the institutional information used for decision-making. First, the strategic planning process chronology was marked by four significant incidents. The significant incidents were the Planning Council creation, the Strategic Planning Council creation, gathering institutional information that was placed into two large books, and taking the books to the Strategic Planning Retreat where the gap analysis was conducted and strategic priorities drafted. The four significant incidents mark places along the strategic planning process where institutional information was important to the strategic planning process. Second, the case study discussed using institutional information for decision-making and extended into exploring how using institutional information for decision-making during the strategic planning process impacted IICC's decision-making processes. The study found institutional information was used by the institution studied throughout the strategic planning process. The institutional information drove strategic planning decision-making. The college wanted to use institutional information in the process, collected it, and used it to determine institutional gaps which led to drafting the strategic priorities. The strategic planning process impacted the college's decision-making processes because the institution has more sophisticated decision-making processes. Decision-making is more developed, more complex, and more refined. In order to now make decisions, institutional information is consulted.
Keywords: community colleges; school administration; educational administration; community college education